Neighbourhood walking tours for physicians-in-training. Issue 1156 (7th December 2020) - Cross, Jeremiah Joseph; Arora, Anita; Howell, Benjamin; Boatright, Dowin; Vijayakumar, Pavithra; Cruz, Lee; Smart, Jerry; Spell, Virginia; Greene, Ann; Rosenthal, Marjorie
Abstract: Social and economic factors have a profound impact on patient health. However, education about these factors has been inconsistently incorporated into residency training. Neighbourhood walking tours may help physician-residents learn about the social determinants of health (SDoH). We assessed the impact of a neighbourhood walking tour on physician-residents' perceptions of SDoH, plans for counselling patients and knowledge of community resources. Using a community-based participatory research approach, in 2017 we implemented a neighbourhood walking tour curriculum for physician-residents in internal medicine, internal medicine/primary care, emergency medicine, paediatrics, combined internal medicine/paediatrics and obstetrics/gynaecology. In both pre-tour and post-tour, we asked participants to (1) rank the importance of individual-level and neighbourhood-level factors affecting patients' health, (2) describe strategies used to improve health behaviours and (3) describe knowledge of community resources. Eighty-one physician-residents participated in walks (pre-tour surveys (93% participation rate (n=75)), and post-tour surveys (53% participation rate (n=43)). Pre-tour, the factor ranked most frequently affecting patient health was 'access to primary care' (67%) compared with post-tour: 'income' (44%) and 'transportation' (44%). In describing ways to improve diet and exercise, among pre-tour survey respondents, 67% discussed individual-level strategies and 16% discussed neighbourhood-level, while among post-tour survey respondents, 39% of respondents discussed individual-level strategies and 37% discussed neighbourhood-level. Percentage of respondents aware of community resources changed from 5% to 76% (p<0.001). Walking tours helped physician-residents recognise the importance of SDoH and the value of community resources, and may have broadened frameworks for counselling patients on healthy lifestyles.